2012
DOI: 10.1177/1043454212451365
|View full text |Cite
|
Sign up to set email alerts
|

The Needs of Siblings of Children With Cancer

Abstract: Findings from research studies on the needs of siblings of children with cancer have highlighted the imperative that these siblings be supported and involved in the plan of care when a diagnosis of cancer is made. However, few studies have included the perspective of the nurse when evaluating sibling needs or identifying interventions used to meet the needs. This qualitative descriptive study used a combination of individual interviews and a focus group to capture perspectives from 13 pediatric oncology nurses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(92 citation statements)
references
References 24 publications
4
85
0
3
Order By: Relevance
“…Similar to the findings by Lövgren et al (2016), O'Shea et al (2012 reported that siblings did not want to be left out, and school-age and adolescent siblings often wanted to help the ill child by participating in their care. Similar to the findings by Lövgren et al (2016), O'Shea et al (2012 reported that siblings did not want to be left out, and school-age and adolescent siblings often wanted to help the ill child by participating in their care.…”
Section: Need For Informational and Special Desiressupporting
confidence: 76%
“…Similar to the findings by Lövgren et al (2016), O'Shea et al (2012 reported that siblings did not want to be left out, and school-age and adolescent siblings often wanted to help the ill child by participating in their care. Similar to the findings by Lövgren et al (2016), O'Shea et al (2012 reported that siblings did not want to be left out, and school-age and adolescent siblings often wanted to help the ill child by participating in their care.…”
Section: Need For Informational and Special Desiressupporting
confidence: 76%
“…Honest and open communication has consistently been found to help youth who are grieving the illness, dying, or death of someone close to them 12,13,19,23]. Youth of all ages benefit from living in an environment where they feel safe asking their questions and sharing their feelings about cancer, dying, death, and grief.…”
Section: The Benefits Of Open Communicationmentioning
confidence: 97%
“…Many siblings of children with cancer display signs of anxiety, worry, and guilt [12]. Following the death of a brother or sister, parents have described their child's grief experience as involving anger, sadness, and a profound missing of the sibling [13].…”
Section: Impact On Youthmentioning
confidence: 99%
See 2 more Smart Citations